Optimal co‐placement method considering non‐homogeneous PMU channel capacities. Issue 5 (19th June 2020) - Okekunle, Dahunsi J.; Unigwe, Obinna; Kiprakis, Aristides E.
Abstract : In this study, a topology defragmentation method is developed for co‐placements of phasor measurement units (PMUs) and their communication infrastructure. Electric power networks are defragmented into sets of branches and a realistic cost model, based on reports from industry, is developed. Instead of considering channel limitations, more practical consideration of the presence of dual‐use line relays and PMUs with different channel capacities is used to obtain a least‐cost solution for specified levels of observability. Formulations are proposed to address budget limitations, to maximise benefits from add‐on application, and to enhance application‐sensitive deployments. The approach is demonstrated on a number of IEEE test networks and results reflect practical situations where optimal solutions (especially PMU buses and the capacity of deployed PMUs) depend on the availability of equipment, existing devices, and the level of observability specified. Solutions obtained to specify the bus, branch, PMU type, and phasor data concentrator to connect to and are optimal without the need for algorithmic parameter tuning. It is established, among other conclusions, that placement results should transcend beyond mere statements of the number of installations, but on the specifics of the deployments at the buses, branches, and storage locations.